Expanding the Model: Would it be Possible to Consume Enough Low-Alcoholic Beer to Reach the UK Legal Driving Limit? - Chandla, Danny (Journal of Interdisciplinary Science Topics, 2017)
In a previous paper it was found that 51 litres or 115 cans of low-alcoholic beer would be required to reach the UK legal alcohol limit for drivers [1]. However, the model employed was too simple. This paper explores whether it would be possible to consume the volume required by considering the rate of metabolism of alcohol to determine what volume would be required to reach the limit and maintain it within 1 hour. This was found to 53 litres, which is more than 25 times larger than the average drinking speed of an average UK male.